INSTRUMEN ANGKET SELF-ESTEEM MAHASISWA DITINJAU DARI VALIDITAS DAN RELIABITAS - Rina Dwi Setyawati (Phenomenon : Jurnal Pendidikan MIPA, 2017)
One of the important thing in a study is instrument. There are several forms of instruments that can be used to measure student’s self-esteem. One of them is a questionnaire. Self-esteem Questionnaire developed to measure the aspects of self-esteem, i.e: significance, competence, power, and virtue. Validity evidenced from the self-esteem questionnaire includes content validity and construct validity. Content validity is evidenced in face validity and logical validity. Validation results on the content validity are appropriate questionnaire to be used after 2, 3, 5, 6, 8, 9, 10, 11, 13, 14, 15, 26, 29, and 30 revised. The result of construct validity is model factor as a whole according to p-Chi-Square 0.05, RMSEA≤0,08, NNFI 0,9, CFI 0,9, and IFI 0,9. The test results of these parameters individually show each path having a value of t 1.96 so that the paths are significant. This can be interpreted as a fit model factor and does not need to be done. Calculation of self-esteem questionnaire results obtained reliability  and standard error measurement . The value in question is the self-esteem questionnaire score of the student is likely to be 4.34 points above or below the actual score.